Determination of the anodic dissolution dependencies of a multicomponent alloy as the product of printed circuit board processing in electrolytes based on sulphuric and methanesulfonic acid - Kotok, Valerii; Kucher, Vadym; Sknar, Yuri; Sknar, Irina; Demchyshyna, Oksana; Chasova, Ella (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is the process of anodic dissolution of a multicomponent metallic alloy obtained from the recycling of printed circuit boards (PCBs). Such feedstock consists mainly of copper, tin, nickel, lead, and iron, which complicates its subsequent hydrometallurgical processing and requires the selection of an efficient electrolyte for the initial dissolution stage. A key challenge of the first processing stage is converting alloy components into a soluble form, which can be intensified by selecting an appropriate electrolyte composition and current density. To enhance the rate of electrochemical dissolution, a methanesulfonic acid electrolyte was used for this alloy composition. The results were compared with those obtained in a sulfuric acid electrolyte. Electrochemical characteristics were determined using cyclic voltammetry at different potential scan rates. Qualitative and quantitative evaluation of the anodic process was performed by analyzing cyclic voltammograms and the specific charge consumed during dissolution. The surface composition of the alloy before and after dissolution was determined by X-ray fluorescence analysis, while the composition of the electrolyte after electrolysis was used to evaluate the relative amounts of metals transferred into solution. It was shown that anodic dissolution of the alloy proceeds more intensively in the methanesulfonic acid electrolyte than in the sulfuric acid medium. The specific charge associated with the anodic process was found to be 2–3 times higher in the methanesulfonic acid solution. It was established that during dissolution in a 1 M methanesulfonic acid electrolyte, copper and nickel dissolve mainly, whereas tin and lead accumulate on the surface as low-soluble products. After electrolysis, the alloy surface became enriched in tin and nickel, while the surface deposit contained elevated amounts of tin and lead. These findings indicate the selective nature of the process and the possibility of partial component separation as early as the first stage of electrochemical processing. The results obtained may be applied to the development of recycling technologies for multicomponent alloys, generally consisting of copper, nickel, tin, and lead